Analysis of Accounting Treatment of Accounts Receivable at PT. Palembang Primary Primary Source - Sri Hartati; Alamsyah (Formosa Journal of Multidisciplinary Research, 2022)
This study aims to determine how the recognition, measurement, recording, presentation and disclosure of accounts receivable during 2015 , 2016, and 2017 PT . Primary sources Raya Palembang, The research method that has been done is to collect information report data L/R, balance sheet , a list of accounts , list of assets 2015-2017 and procedures and corporate policies . The results showed recognition of the calculation of accounts receivable has been running well , trade receivables obtained by calculating the 200 hours of work tools multiplied by the value of the contract agreement , so on the journal accounts receivable in debit and reception services equipment rental in the credits , the presentation of accounts receivable the company has not made a backup of receivables business.